PENGARUH CORPORATE GOVERNANCE, INCOME SMOOTHING, LEVERAGE DAN AUDIT FEE TERHADAP TAX AVOIDANCE - Putri, Widya Nastiti Sari Rusna; Kalbuana, Nawang; Tarigan, Pelinta (Pascasarjana Universitas Sultan Ageng Tirtayas, 2024)
Indonesian as a developing country, needs taxes to boost the country's economy. Tax avoidance is regarded as the action of taxpayers to avoid the great value of the tax deposited. The way the taxpayer usually does is by making a profit statement up to raising the cost of consultancy services. The aim of this study is to find out the impact of Corporate Governance, Income Smoothing, Leverage, and Audit Fee on Tax Avoidance on energy companies listed on the Indonesian Stock Exchange during the period 2018-2022. The data in this research is secondary data and the research method uses quantitative methods. Sample determination using purposive sampling and obtained 9 companies that became final samples in the five-year observation period, namely 2018-2022. Data analysis in this study uses double regression analysis using the SPSS 25 program. The results of this research indicate that partially the Corporate Governance variable which is proxied by the Independent Board of Commissioners (X1), Audit Committee (X2), and Audit Fee (X5) has no effect on Tax Avoidance with only obtaining sig values of 0.117, 0.549 and 0.279. Meanwhile The Income Smoothing variable (X3) with a value of 0.031 has a significant and positive effect on Tax Avoidance. The Leverage variable (X4) has a significant and negative effect on Tax Avoidance with a sig value of 0.016.